A NORMATIVE REVIEW OF ISLAMIC LAW ON UNDERAGE MARRIAGE: AN EXAMINATION OF AGE CRITERIA AND ITS IMPLICATIONS FOR DOMESTIC LIFE - Muhammadong Muhammadong (Yayasan Nuraini Ibrahim Mandiri, 2026)
Child marriage is still a problem in many cultures, even those that follow Islamic law. This practice is frequently shaped by social, economic, and cultural considerations, along with various theological interpretations. Islamic law does not explicitly stipulate a minimum age for marriage; rather, it underscores physical and psychological maturity as the principal criteria. This study seeks to evaluate the suitability of underage marriage through a normative analysis of Islamic law and to investigate its implications within domestic life. The methodology employed is normative legal research utilizing conceptual and statutory frameworks, executed through literature reviews of Islamic legal sources and relevant laws. The findings suggest that while textual provisions exist, the idea of public welfare (maslahah) in Islamic law underscores the need of mental, emotional, and economic preparedness. Early marriage can lead to a number of bad things, such unhappy marriages, more divorces, and health problems for both the mother and the kid. Consequently, a more contextual normative reinterpretation is essential to ensure the optimal realization of marriage's objectives specifically, the development of a peaceful, loving, and compassionate family.